2019
DOI: 10.1111/jpi.12603
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects mouse oocytes from DNA damage by enhancing nonhomologous end‐joining repair

Abstract: Mammalian oocytes remain arrested at the first prophase of meiosis in ovarian follicles for an extended period. During this protracted arrest, oocytes are remarkably susceptible to the accumulation of DNA damage. Melatonin (N-acetyl-5-methoxytryptamine), a hormone secreted by the pineal gland, has diverse effects on various physiological processes. However, the effect of melatonin on DNA damage response in mammalian oocytes has not been explored. Here, we showed that melatonin protected mouse oocytes from DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…We proposed that melatonin supplementation leads to the remodeling of the metabolic framework balance that supports oocyte development by promoting the proliferation of cumulus cells and maintaining the communication coupling. Indeed, a large number of studies have shown that melatonin can be used to ameliorate oxidative stress-associated meiotic defects by protecting mitochondrial function in maternally aged oocytes [ 30 , 40 , 41 ]. An improved mitochondria function, in turn, act on melatonin synthetic enzymes, regulating melatonin biosynthesis and free radical scavenger, thus completing a feedback regulatory loop [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We proposed that melatonin supplementation leads to the remodeling of the metabolic framework balance that supports oocyte development by promoting the proliferation of cumulus cells and maintaining the communication coupling. Indeed, a large number of studies have shown that melatonin can be used to ameliorate oxidative stress-associated meiotic defects by protecting mitochondrial function in maternally aged oocytes [ 30 , 40 , 41 ]. An improved mitochondria function, in turn, act on melatonin synthetic enzymes, regulating melatonin biosynthesis and free radical scavenger, thus completing a feedback regulatory loop [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin, now known to be a robust antioxidant that protects against abnormalities in the mitochondrial fragmentation and spindle ( Reiter et al, 2016 ), was subsequently shown to increase IVM and in vitro fertilization (IVF) rates in mice ( Leem et al, 2019 ), pigs ( Chen et al, 2020 ), cows ( Liang et al, 2017a ), and humans ( Tamura et al, 2008 ). Melatonin has been shown to defend against attenuated kinetochore–microtubule attachment stability, disrupting spindle assembly, and chromosome alignment from toxic chemicals such as benzo[ghi]perylene and bisphenol A in mouse oocytes ( Zhang et al, 2017 ; Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reiter et al, 65 reported that the first primary function of melatonin is to protect cells from oxidative stress, avoiding DNA, RNA, proteins, and membrane cell damage through its free radical scavenger capacity. Melatonin protects oocytes from DNA damage during prophase arrest by enhancing DNA repair via non-homologous end-joining (NHEJ) pathway and subsequently prevents the deterioration of oocyte quality during meiotic maturation 66 . In the same trend, it had been found that melatonin enhances the repair of oxidized DNA.…”
Section: Discussionmentioning
confidence: 99%